Reading Further Between The Lines – Recent Developments in the UK MOD Acquisition Requirements & Acceptance Tube Map. Issue 1 (16th August 2018) - Gibson, Ian; Blake, Ian; Williams, Samantha; Price, Andrew
Abstract: How do you visualise a very large complicated problem? With a very large complicated diagram obviously! But what if the diagram used a familiar notation that needed little or no explanation? What if the subject matter could be carved up into distinct interwoven threads that would be easily recognised by the reader? Welcome to the MOD Acquisition Requirements & Acceptance Tube Map. The authors have been engaged in a task to rewrite the UK Ministry Of Defence (MOD) Acquisition System Guidance intranet site for Requirements, Test, Evaluation and Acceptance. Whilst the task has resulted in a major overhaul of the guidance, it has been underpinned by a novel depiction of parallel threads of Requirements; Test, Evaluation & Acceptance; Portfolio, Programme and Project Management (P3M); and Solution Development ‐ running through the parallel interrelated lifecycles of Programme Management (based on the Generic Capability Model) and Project Management (based upon the CADMID lifecycle – Concept, Assessment, Demonstration, Manufacture, In‐Service, Disposal). This has taken the form of an underground "tube map" with lines representing stakeholder communities, minor stations representing technical activities, callout boxes for work products, and interchange stations representing review points.